Motor performance after treatment of pilocytic astrocytoma in the posterior fossa in childhood. Issue 8 (12th October 2021) - Kristiansen, Ingela; Frykberg, Gunilla E.; Höglund, Anette; Sondell, Annette; Strömberg, Bo; Frisk, Per
Abstract: Background: Pilocytic astrocytoma is the most common brain tumour type in childhood located in the posterior fossa, and treated mainly with surgery. These tumours have low mortality, but knowledge concerning its long‐term outcome is sparse. Aims: The aim was to investigate if patients treated for pilocytic astrocytoma in the posterior fossa had motor complications, including balance, motor and process skills. Methods and Results: This descriptive single‐centre study includes eight children and 12 adults, treated for pilocytic astrocytoma as children. Motor performance was investigated with Bruininks–Oseretsky Test of Motor Proficiency, Second Edition, and dynamic balance with the mini‐balance evaluation systems test. Physiological cost index, six‐minute walk test, hand grip strength and assessment of motor and process skills were also evaluated. Ten patients reported motor difficulties, mainly from the upper limbs. The motor performance test showed results within normal limits except for manual dexterity, which was significantly below mean ( p = .008). In the dynamic balance test patients had significantly lower results compared with controls ( p = .036). Physiological cost index, six‐minute walk tests and hand grip strength showed results within normal limits. In the Assessment of Motor and Process Skills, patients over 16 years had significantly lower results compared with test norms for motor activities of daily living (ADL) and 30% of all patients scored below the cut‐off level for difficulties with motor skills. Conclusions: Motor performance for patients treated for pilocytic astrocytoma in the posterior fossa in childhood is satisfactory but some patients display difficulties with balance, manual dexterity and ADL motor skills. Thus, it is important to identify those in need of motor follow‐up and training.